101k views
4 votes
How to solve 2x - 3x/2 = -x + 1/3
PLZ HELP!

2 Answers

0 votes
I got 2/3 .... Is it correct? Seems weird...
User Max Wolfen
by
5.0k points
4 votes

2x - 3x/2 = -x + 1/3

first, we can multiply both sides by 2 in order to get rid of the 2 under 3x

2(2x-3x/2) = 2(-x + 1/3)

4x - 3x = -2x + 2/3

now we combine like terms

x = -2x + 2/3

and we can add 2x to both sides

3x = 2/3

now we divide by 3 on both sides

x = 2/9

hope this helps

User Todd Anderson
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.